Relação antigênica entre alfaherpesvírus caprino 1 (CpHV-1) e alfaherpesvírus bovino 1 (BoHV-1) e infecção experimental de cabritos e bezerros com o CpHV-1 - Martins, Bruno (2019)
Caprine alphaherpesvirus 1 (CpHV-1), family Herpesviridae, genus Varicellovirus is genetically and antigenically related to Bovine alphaherpesvirus 1 (BoHV-1). In kids, CpHV-1 infection has been associated with gastroenteric and respiratory diseases, whereas in adult the infection is usually subclinical or associated with abortions. Here, we investigated further the antigenic relationships of CpHV-1 with BoHV-1 and the pathogenesis of CpHV-1 in goats and calves. The antigenic relationship between CpHV-1 and BoHV-1 was analyzed by reactivity with monoclonal antibodies (MAbs) and by virus-neutralizing assays (VN). Reactivity of MAbs revealed that CpHV-1 and BoHV-1 share epitopes on the major envelope glycoproteins, e.g. gB, gC and gD. Additionally, the antigenic relationship was demonstrated by VN assays, when cross neutralization was observed between the viruses. On these tests, BoHV-1 antisera neutralized CpHV-1 more efficiently than CpHV-1 antisera neutralized BoHV-1. The antigenic relationship between CpHV-1 and BoHV-1 may have impact in serological diagnosis and control. The pathogenesis of CpHV-1 (Isolate WI 13- 46) was studied in experimentally infected kids and calves. For this, seven four to six-months-old kids, and twelve calves (six to eight-months-old), were inoculated intranasally (IN) with WI 13-46 isolate (5x107,6 infective doses, TCID50). After inoculation, clinical, serological and virological monitoring were performed. The seven kids inoculated with CpHV-1 presented nasal secretion between day 3 and 14 post-infection (pi) and respiratory distress between days 5 and 8 pi. The virus was isolated from the nasal swabs of all kids between day 1 and 9 pi. In order to verify the reactivation of the latent infection, on day 36 pi, the animals were treated with dexamethasone (Dex, 0.4mg/Kg/day) for 5 days and monitored for 15 subsequent days. Administration of Dex did not result in virus excretion in nasal secretions nor in increase in neutralizing antibodies titers. However, latent infection had been established, as evidenced by detection of CpHV-1 DNA in the trigeminal ganglia (TG) and olfactory bulbs (OB) of kids euthanized on day 67 pi. On the other hand, inoculation of CpHV-1 in calves did not result in viral replication/excretion, clinical signs or seroconversion. Overall, these results demonstrate that: i) CpHV-1 and BoHV-1 are antigenically related; ii) CpHV-1 (WI 13-46) replicates efficiently in kids and may produce mild to moderate respiratory disease after IN inoculation; iii) CpHV-1 establishes latent infection in TG and OB of kids but was not reactivated following standard herpesviruses reactivation protocols; and iv) Calves were not susceptible to CpHV-1 infection after IN inoculation. Finally, these results helped in understanding the antigenic relationships among animal herpesviruses and pathogenesis of CpHV- 1 infection in kids and calves.